H2 Generation from a homogeneous photocatalytic system containing noble‐metal‐free Co(II) complex under the irradiation of visible light. (1st June 2014) - Rao, Heng; Wang, Zhi‐Yuan; Wang, Jun; Hu, Xiao‐Zong; Fan, Yao‐Ting; Hou, Hong‐Wei
SUMMARY A noble‐metal‐free molecular catalyst, [Co(dmbp)3]Cl2 (dmbp = 4, 4'‐dimethyl‐2, 2'‐bipyridyl) was prepared for photocatalytic H2 generation. A three‐component photocatalytic system was constructed by combination of [Co(dmbp)3]Cl2 as catalyst, Eosin Y as photosensitizer and triethylamine as sacrificial electron donor to give an efficient H2 generation system under visible‐light irradiation (λ > 420 nm). The maximum H2 yield was up to 249.2 turnover number (vs. catalyst) over 2 h irradiation under the conditions with catalyst of 4.0 × 10−4 M, 10% TEA (v/v), EY2− of 4.0 × 10−4 M and pH 10 in MeCN/H2O (1 : 1, v/v). Furthermore, the dynamics behaviors of the photolysis system were also briefly discussed. Copyright © 2014 John Wiley & Sons, Ltd.